Cooperative Knowledge and Member Motivation for Member Participation (Study on the Best Cooperative in Sedong District) - Shella Fitri Anggraeny; Rifa Dwi Safitri; Anna Suzana (Universitas KH. Abdul Chalim Mojokerto, 2025)
Cooperatives have an important role as one of the pillars in Indonesia's economic development, which is based on the principles of kinship and mutual cooperation. This research was conducted with the aim of finding out the knowledge of cooperatives and members' motivation for member participation in KUD BUKTI. This study also uses an associative quantitative method with a simple random sampling technique calculated based on the Slovin formula. From a total population of 4,778 members, this study produced a sample of 369. SMARTPLS software was used to collect data using a Likert scale questionnaire and analyze it using the SEM-PLS (Structural Equation Modeling-Partial Least Squares) method. The study’s findings revealed that